2018
DOI: 10.3389/fpsyt.2018.00436
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Resilience as Mediators Between Stress and Life Satisfaction Among People With Substance Use Disorder in China

Abstract: This study investigated the potential mediating roles of resilience and social support in the relationship between stress and life satisfaction. A total of 426 individuals, who have substance use disorder, from the Shifosi and Dalianshan rehabilitation facilities in China participated in the study. They were tested using the Perceived Stress Scale, Multidimensional Scale of Perceived Social Support, Connor–Davidson Resilience Scale, and Satisfaction with Life Scale. Results showed that the serial multiple medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 71 publications
(76 reference statements)
8
62
2
2
Order By: Relevance
“…Therefore, it is an expected result that life satisfaction is positively associated with resilience. In addition, there are some studies revealing that resilience is associated with self-esteem and hopelessness ( Karatas & Savi-Çakar, 2011 ); psychological well-being ( Ifeagwazi et al, 2014 ); life satisfaction ( Akbar et al, 2014 ; Jokar, 2007 ; Şahin Baltacı & Karataş, 2015 ); meaning in life and hope ( Halama, 2014 ; Kim et al, 2005 ); hope and life satisfaction ( Shetty, 2015 ; Yang et al, 2018 ) and hope ( Duggal et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is an expected result that life satisfaction is positively associated with resilience. In addition, there are some studies revealing that resilience is associated with self-esteem and hopelessness ( Karatas & Savi-Çakar, 2011 ); psychological well-being ( Ifeagwazi et al, 2014 ); life satisfaction ( Akbar et al, 2014 ; Jokar, 2007 ; Şahin Baltacı & Karataş, 2015 ); meaning in life and hope ( Halama, 2014 ; Kim et al, 2005 ); hope and life satisfaction ( Shetty, 2015 ; Yang et al, 2018 ) and hope ( Duggal et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These individuals participate in social changes and activities, they are faithful; many have the ability to extract meaning and benefits from the troubles, traumas and worries in their lives. The existing research has revealed that resilience is associated with problem solving ( Neenan & Dryden, 2012 ); stress and exhaustion ( Hao et al, 2015 ); locus of control ( Dunn & Brody, 2008 ); family support ( White et al, 2008 ); social support ( Nikmanesh & Honakzehi, 2016 ; Şahin Baltacı & Karataş, 2015 ); hope ( Duggal et al, 2016 ); pessimism and positive affectivity ( Tugade & Fredrickson, 2004 ) and life satisfaction ( Akbar et al, 2014 ; Şahin Baltacı & Karataş, 2015 ); depression ( Şahin Baltacı & Karataş, 2015 ), self-esteem and hopelessness ( Karatas & Savi-Çakar, 2011 ), hope and life satisfaction ( Shetty, 2015 ); life satisfaction, stress and social support ( Yang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, we found that higher level of PSS was associated with lower prevalence of depressive symptoms, which is similar to the findings that social support has a protective effect on college students’ anxiety symptoms during COVID-19 pandemic [ 15 ]. As a positive psychological resource, PSS is closely related to an individual’s health and well-being [ 14 ]. As a special group, college students’ physical and mental development is not mature, and they are more likely to have psychological problems during the epidemic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some experts have already appealed for more researches from the perspective of positive psychology to deal with the mental health crisis caused by the COVID-19 pandemic [ 13 ]. Perceived social support (PSS) is one of the most important psychological resources to cope with challenging life events [ 14 ]. Social support has been reported to have a protective effect on college students’ mental health [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exclusion and social rejection can lead to lower selfesteem, self-efficacy and individual´s overall health, as well as mental diseases, such as depression and anxiety [119,120]. Regarding SUD, a positive social network has been shown to be beneficial for abstinence and recovery, whereas people with poor family relationships and low social support have been proved to be more prone to use drugs [121][122][123][124]. In particular, it is the quality of relationships with family, friends and significant others and not the quantity which can buffer SUD behaviors [121].…”
Section: Social Supportmentioning
confidence: 99%